Coronal Lateral Collateral Ligament Sign: A Novel Magnetic Resonance Imaging Sign for Identifying Anterior Cruciate Ligament–Deficient Knees in Adolescents and Summarizing the Extent of Anterior Tibial Translation and Femorotibial Internal Rotation. Issue 4 (March 2021) - Mitchell, Brendon C.; Siow, Matthew Y.; Bastrom, Tracey; Bomar, James D.; Pennock, Andrew T.; Parvaresh, Kevin; Edmonds, Eric W.
Background: Incompetence of the anterior cruciate ligament (ACL) confers knee laxity in the sagittal and axial planes that is measurable with clinical examination and diagnostic imaging. Hypothesis: An ACL-deficient knee will produce a more vertical orientation of the lateral collateral ligament (LCL), allowing for the entire length of the LCL to be visualized on a single coronal slice (coronal LCL sign) on magnetic resonance imaging. Study Design: Cohort study (diagnosis); Level of evidence, 3. Methods: Charts were retrospectively reviewed from April 2009 to December 2017 for all patients treated with ACL reconstruction (constituting the ACL-deficient cohort). A control cohort was separately identified consisting of patients with a normal ACL and no pathology involving the collateral ligaments or posterior cruciate ligament. Patients were excluded for follow-up <2 years, incomplete imaging, and age >19 years. Tibial translation and femorotibial rotation were measured on magnetic resonance images, and posterior tibial slope was measured on a lateral radiograph of the knee. Imaging was reviewed for the presence of the coronal LCL sign. Results: The 153 patients included in the ACL-deficient cohort had significantly greater displacement than the 70 control patients regarding anterior translation (5.8 vs 0.3 mm, respectively; P < .001) and internal rotation (5.2° vs −2.4°, P < .001). Posterior tibial slope was not significantly different. The coronal LCL sign was present in a greater percentage of ACL-deficient knees than intact ACL controls (68.6% vs 18.6%, P < .001). The presence of the coronal LCL sign was associated with greater anterior tibial translation (7.2 vs 0.2 mm, P < .001) and internal tibial rotation (7.5° vs –2.4°, P = .074) but not posterior tibial slope (7.9° vs 7.9°, P = .973) as compared with its absence. Multivariate analysis revealed that the coronal LCL sign was significantly associated with an ACL tear (odds ratio, 12.8; P < .001). Conclusion: Our study provides further evidence that there is significantly more anterior translation and internal rotation of the tibia in the ACL-deficient knee and proves our hypothesis that the coronal LCL sign correlates with the presence of an ACL tear. This coronal LCL sign may be of utility for identifying ACL tears and anticipating the extent of axial and sagittal deformity.